Pengaruh Kompensasi Terhadap Produktivitas Karyawan Di PT. Dwipa Manunggal Kontena - Sumarsid Sumarsid (STIKOM CKI, 2016)
This study aims to determine how the compensation effect on the productivity of employees at PT. Dwipa Manuggal containers. Based on the analysis of the correlation coefficient r value of 0.904 obtained thereby providing compensation showed a very strong and significant relationship 0.000> 0.05 on the productivity of employees at PT. Dwipa Manuggal containers, relations between the two variables and positive direction means that any increase or decrease in compensation will be followed by an increase or decrease in the productivity of employees at PT. Dwipa Manuggal containers. Based on the analysis of the results obtained determinant coefficient 81.7% means that compensation has contributed greatly to the rise and fall productivity of employees at PT. Dwipa Manuggal containers, while the remaining 28.3% is influenced by factors other than compensation not I researched include: job stress, motivation and leadership styles. Calculation analysis of hypothesis testing by t test (partial) obtained results that to> t table (11.181> 1.701) These results can be concluded that to> tα. As well as the significant value of 0000 <5% (0.000 <0.05). Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted on a real level (level of significance) of 0.05 indicates that the hypothesis that the writer suggested that allegedly exist between the compensation effect on the productivity of employees at PT. Dwipa Manuggal containers have been proven.